Dampak Kemacetan di Kota Bandung bagi Pengguna Jalan - Rinaldy Akhmad Hermawan; Ria Haryatiningsih (UNISBA Press, 2022)
Abstract The city of Bandung is a destination for tourists who want to enjoy a vacation, the cold weather and friendly people make the city of Bandung always a tourist destination by several domestic and foreign tourists. In addition, the city of Bandung also has its own charm for the community to be used as a place to live. This causes an increase in the number of vehicles in the city of Bandung which is quite high which causes congestion at several points, one of which is around the Pasteur toll gate. According to the Asia Development Bank (ADB), Bandung is the most congested city, even beating other big cities.This has resulted in congestion on a number of roads in the city of Bandung. T this researcher aims to determine the impact of traffic jams on the road around the Pasteur toll gate, Bandung City, using a linkert scale analysis and conducting several interviews to find out the actual conditions in the field. The results of the study show that the consequences of traffic jams have 3 impacts, namely economic, social and environmental impacts. The linkert analysis score on social impact is 91.4%, which means that congestion is “Highly Impactful” on the social side. The linkert analysis score is 86.43%, thus also the “Highly Impacting” congestion on the economic side. The results of the linkert analysis on the environmental impact of 84.8% which means that the traffic jam is